Brevity and Ellipsis: An Applied Study in the Holy Quran (Journal of the College of Basic Education, 2026)
This research presents a rhetorical and applied study of brevity (Ījāz) in the Holy Qur’an, focusing on its two main types: brevity through conciseness (Ījāz al-Qaṣr) and brevity through omission (Ījāz al-Ḥ). The study begins by defining brevity linguistically and technically, explaining its rhetorical purposes and its significant role in conveying profound meanings through few words.The first section examines Ījāz al-Qaṣr, clarifying its concept and highlighting Qur’anic examples that demonstrate how extensive meanings are expressed without omission, such as the verse “And in retribution there is life for you”, which encapsulates deep moral and legal implications in concise wording.The second section addresses Ījāz al-Ḥadhf, explaining its conditions and various forms, including the omission of letters, subjects, predicates, objects, and entire clauses. Numerous Qur’anic examples are analyzed to illustrate how meaning remains complete and clear through contextual and linguistic indicators.The study concludes that Qur’anic brevity represents the highest level of eloquence, as it combines clarity, depth, and precision without redundancy. It also affirms that omission in the Qur’an is never arbitrary but guided by rhetorical purpose and contextual evidence, which reinforces the miraculous nature of the Qur’anic style and its unmatched eloquence.